Teachers’ Strategies in Increasing Children’s Participation in Group Learning Activities at PAUD Shihabul Musthofa Merangkak, Embung Kandong Village - Yuliana Susanti; Baiq Nurhayani (Formad English Foundation NTB-Jakarta, 2025)
This study aims to describe teachers’ strategies for enhancing children’s participation in group learning activities at PAUD Shihabul Musthofa Merangkak, Embung Kandong Village, and to analyze the impact of the strategies implemented. Using a qualitative descriptive approach, the research collected data through observation, semi-structured interviews, and documentation, involving teachers, children, and parents selected via purposive sampling. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that teachers planned group learning strategically by aligning weekly themes with developmental indicators and considering children’s age, characteristics, and individual needs. Implementation involved varied and engaging methods such as role-playing, group projects, singing, storytelling, and assigning specific roles to ensure participation from all children, including those typically quiet or hesitant. Evaluation and reflection were conducted through daily observations, developmental notes, and parental input, enabling teachers to refine instructional practices continuously. The implementation of these strategies resulted in increased enthusiasm, confidence, and active engagement among children, reflected in their enjoyment of collaborative tasks, improved communication, and stronger peer interaction. Parents also reported positive behavioral changes at home, including greater openness and eagerness to share learning experiences. These results indicate that contextually adapted, play-based, and interactive strategies can effectively strengthen children’s participation in group learning settings, particularly in rural early childhood education contexts.